A Suggested Fracture Classification of Adult Small Animal Fractures - Prieur, W. D.; Braden, T. D.; v. Rechenberg, Brigitte (Veterinary and Comparative Orthopaedics and Traumatology, 1990)
A classification system for fractures of long bones in adult small animals is described. Its application is demonstrated in some femur fractures. This classification system will be expanded later on to other bones like pelvis, spine, distal limb bones, and to fractures of the growing animals.
Keywords: Fracture; Fracture classification